Riverbank lupine’s (Lupinus rivularis) influence on conifer growth, ectomycorrhizal colonization, and neighboring vegetation in coarse sediments left behind after dam removal - Kardouni, James; Danilchik Lindsay, Maile; Labay, Andrew; Bauman, Jenise M. (Frontiers in Ecology and Evolution, 2023)
Until recently, much of the Elwha River was inaccessible to anadromous fish species due to the Elwha and Glines Canyon Dams. Dam deconstruction resulted in approximately 325 hectares of formerly inundated lake beds devoid of natural riparian corridors or adjacent forests.Efforts to restore the vegetation have had varying success. Areas where fine sediments settled along the valley walls quickly regenerated, while coarse terraces were slower to revegetate from plantings and directed seeding. One seeded species, riverbank lupine (Lupinus rivularis), quickly established on the coarse-textured terraces. Riverbank lupine is a pioneering species that assimilates nitrogen (N) through N-fixing bacteria, thus it enriches the soil with bioavailable N and organic matter upon decomposition. The goal of this study was to investigate lupine's influence on conifer establishment in the coarse sediments of the former Lake Mills basin along the Elwha River. Conifers planted three years prior to the study in plots with different levels of lupine cover (sparse, medium, or dense) were measured for growth, foliar total nitrogen, and ectomycorrhizal (ECM) root colonization. Soil N, organic matter (OM), and surrounding plant community composition were also evaluated at this time. After three years, conifers did not statistically differ in height or basal diameter among differing levels of lupine cover. However, conifers in the medium-and dense-cover plots had significantly greater foliar N concentrations (β = 0.25, SE = 0.08, P<0.001). The roots of conifers in dense-and medium-cover plots had significantly less ECM colonization than did those in the sparse-cover plots (β = 0.14, SE=0.03, P=0.03). No differences existed regarding soil total N or OM. Plant community composition differed among lupine cover classes (PERMANOVA, (F(2,21) = 2.02, P = 0.01). Higher lupine cover resulted in lower species richness (β = 25.9, SE=0.61, P = 0.04). Based on our findings, the inclusion of native lupine in coarse, N-limiting soils contributes to the N pools without reducing the growth of planted conifers, which may accelerate forest succession leading to closed canopies much faster than passive recovery.